Prevention or promotion?: A research on the advertising communication strategies of P2P lending platforms – an empirical analysis based on panel data. Issue 1 (7th March 2020) - Hou, Min; Gu, Chunmei; Wang, Jiakai; Hou, Ping
Abstract : Purpose: A large number of competitors springing up at the same time is a unique phenomenon to emerging markets. How to promote product sales and improve platform performance through appropriate advertising communication strategies is not only an actual problem for the P2P platforms that are committed to long-term and stable operations but also an academic problem in marketing. Design/methodology/approach: This study collected a total of 1960 pieces of panel data of the P2P platforms and constructed a panel data analysis model after filtering. Findings: The empirical analysis reveals the following: the prevention-focus advertising has a greater impact on platform trading volume, compared with the promotion-focus advertising, and the impact is positively significant; the platform which has a third-party cooperation should use promotion-focus advertising, while prevention-focus advertising is a better choice for the platform without a third-party cooperation. Furthermore, the effects of prevention-focus advertising and promotion-focus advertising on the platforms using individual projects and platforms using organization projects differ. Originality/value: The results of this study have some reference to the selection of advertising communication strategies for the high-risk financial products.